Evolution of human Natural Killer cell receptors - Guinan, Kieran (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2009)
Natural Killer (NK) cells are key components of the innate immune system which function in identifying and destroying aberrant or infected cells. They also play active roles in human reproduction. These functions are largely controlled by the killer immunoglobulin-like receptor (KIR):Human Leukocyte antigen (HLA) receptor:ligand system. KIR inhibit and activate NK cells by interacting with their ligands, HLA epitopes expressed on target cells. KIR and HLA are characterized by high diversity at genetic, phenotypic and functional levels. Many KIR are highly polymorphic with different alleles encoding receptors with contrasting phenotypes, specificity for ligand and function. In addition to the inherent influence of genetic variation on KIR, the presence of HLA class I ligands can also influence expression of these receptors. The importance of NK cells and the KIR:HLA receptor ligand system in immunity to infection and in reproduction makes them strong candidates for genes undergoing natural selection in the human genome. In this study, KIR and HLA diversity in humans was investigated. It was hypothesized that these systems are undergoing natural selection and perhaps co-evolving. Two homogeneous Irish cohorts from Belfast and Dublin were typed at high resolution for the presence/absence of KIR genes. KIR polymorphism and HLA class I ligands. The potential for natural selection occurring at the level of gene, polymorphism and haplotype structure was investigated. KIR expression on NK cells was also investigated by flow cytometry and examined with respect to polymorphism and HLA class I ligand status.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin